2009
DOI: 10.1111/j.1540-4781.2009.00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Languaging: University Students Learn the Grammatical Concept of Voice in French

Abstract: In this article we explore the process and product of languaging as it concerns the learning of the grammatical concept of voice (active, passive, and middle) in French. We examine and analyze the amount and type of languaging produced by a small sample of university students as they struggle to understand the concept of voice. Students who are high languagers learn about the grammatical concept of voice in French with greater depth of understanding than low languagers. We demonstrate that there is a relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
147
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(171 citation statements)
references
References 18 publications
16
147
1
2
Order By: Relevance
“…Results showed that both the +WL and the -WL groups outperformed the control group on the immediate or delayed posttest, but only the +WL group scored significantly higher than the control group regarding the result of their delayed posttest, demonstrating the facilitative effect of written languaging. Ishikawa and Suzuki (2016) is similar to Swain et al (2009) in research design, the difference being that different grammar items were targeted and the former involved written languaging while the latter oral languaging. Apparently the status-quo in this respect shows that more studies are warranted to explore the effect of written languaging on the learning of other grammar items by involving longer reading input and output, instead of grammar explanations and sentence translations, respectively in the treatment and posttest.…”
Section: Theory and Practice In Language Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Results showed that both the +WL and the -WL groups outperformed the control group on the immediate or delayed posttest, but only the +WL group scored significantly higher than the control group regarding the result of their delayed posttest, demonstrating the facilitative effect of written languaging. Ishikawa and Suzuki (2016) is similar to Swain et al (2009) in research design, the difference being that different grammar items were targeted and the former involved written languaging while the latter oral languaging. Apparently the status-quo in this respect shows that more studies are warranted to explore the effect of written languaging on the learning of other grammar items by involving longer reading input and output, instead of grammar explanations and sentence translations, respectively in the treatment and posttest.…”
Section: Theory and Practice In Language Studiesmentioning
confidence: 99%
“…The study, adopting a pretest-posttest design, recruited 9 participants who and I-I) as measured by pretests and posttests, which could be attributed to the fact that the former two pairs engaged in a larger amount of and more types of languaging than the latter two pairs/groups. To summarize, all four studies observed the positive learning effect of languaging on grammar understanding and use, and they respectively revealed the impact of learners' existing grammar knowledge (Swain et al, 2009), quantity and quality of languaging , and proficiency pairing/grouping (Li, 2015), as well as the process of cultivating scientific concept about grammar ). Yet, the studies cannot inform us about whether languaging is more effective and efficient than other methods, say, teacher-fronted instruction in facilitating grammar learning since they did not incorporate any control or comparison group.…”
Section: A Studies On Oral Languaging In L2 Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the findings reported to date provide promising evidence that warrants serious consideration of pedagogical alternatives to pervasive ones which rely primarily on discrete, often oversimplified, and even simplistic, pedagogical grammar rules. Examples of these studies include Van Compernolle (2012) who developed materials for the development of sociopragmatic knowledge of L2 French; Yáñez-Prieto (2008) who focused on verbal aspect in Spanish; Negueruela (2003Negueruela ( , 2008 for the development of verbal aspect, mood, and modality in Spanish; Author (2011) who looked at materials for the development of verbal aspect in English; and a series of publications by Swain, Lapkin and colleagues focusing on the concept of voice in French (Knouzi et al 2010, Lapkin et al 2008, Swain 2010Swain et al 2009). For comprehensive and in-depth overviews of studies based on CBI and Systemic-Theoretical Instruction refer to Lantolf andPoehner (2008, 2014).…”
Section: Enhancing Metalinguistic Knowledge Through Pedagogical Artifmentioning
confidence: 99%